The Methods of Uphill Sprint and Downhill Sprint Training Against 100 Meters Running Speed Viewed From the Strength of the Leg Muscles in son Athletes - Kuncoro Hadi Kusumo; Wasis Himawanto; Sulistiono Sulistiono (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The purpose of this study is to find the truth about: (1) To find out the difference in the influence between the Uphill sprint and Downhill Sprint training methods on the improvement of 100-meter sprint achievement. (2) To find out the difference in the improvement of 100-meter sprint achievement between students who have high and low leg muscle strength. (3) To determine the effect of the interaction between the Uphill sprint and Downhill Sprint training methods with the strength of the high and low leg muscles on the improvement of the 100-meter sprint performance. Experimental method in one group without comparison using pretest-posttest design. The population of this study was athletes from SMP Negeri 1 Rejoso, Nganjuk Regency, class VIII. The sample size used in this study was 32 Men athletes. The sampling technique in this study was Purposive random sampling. The variables studied are free variables consisting of two reactors, namely manipulative variables and attributive variables and one dependent variable. Manipulative variables have two treatments, including giving Uphill sprint exercises, and Downhill sprints. While the attributive variable in this study is the strength of the leg muscles which are distinguished by high and low. The dependent variable of the study is the increase in sprints of 100 meters. Data collection techniques with tests and measurements,  leg muscle strength data with leg and back dynamometers. The data analysis techniques used for hypothesis testing are the 2-lane design Variance Analysis (ANOVA) and the Newman-Keuls range test, at a significance level of 95%. The results of the study that Uphill sprint training has a different improvement from Downhill sprint training. From the calculation results obtained Fhit = 12.5641 greater than Ftabel = 2.95 (F0 > Ft) at a signification level of 5%. This means that the null hypothesis (Ho) is rejected. This means that the Uphill sprint practice has different improvements than the Downhill sprint practice is acceptable. The results of this study showed that players who had low leg muscle strength had a 100-meter sprint increase which was different from players who had high leg muscle strength. This is evidenced by the value of Fhit = 4.2619 greater than Ftabel = 2.95 (F0 > Ft) at a signification level of 5%. This means that the null hypothesis (H0) is rejected. This means that athletes who have low leg muscle strength have a 100-meter sprint that is different from high leg muscle strength players, it is acceptable. The results of this study also showed that there was an interaction between the influence of plyometric exercise and a significant level of leg muscle strength, which was shown by F0 = 23.4810 greater than Ft = 2.95 at a signification level of 5% so that H0 was rejected, so it can be concluded that there was a significant interaction between the influence of plyometric exercise and the level of leg muscle strength. Players who have low leg muscle strength are more appropriately given the Uphill sprint training treatment to increase the sprint by 100 meters. Downhill sprint training treatment is more appropriately given to athletes who have high leg muscle strength.